2019
DOI: 10.1002/jor.24459
|View full text |Cite
|
Sign up to set email alerts
|

In‐Vivo Efficacy of Recombinant Human Hyaluronidase (rHuPH20) Injection for Accelerated Healing of Murine Retrocalcaneal Bursitis and Tendinopathy

Abstract: The deposition of aggrecan/hyaluronan (HA)‐rich matrix within the tendon body and surrounding peritenon impede tendon healing and result in compromised biomechanical properties. Hence, the development of novel strategies to achieve targeted removal of the aggrecan‐HA pericellular matrix may be effective in treating tendinopathy. The current study examined the therapeutic potential of a recombinant human hyaluronidase, rHuPH20 (FDA approved for reducing HA accumulation in tumors) for treating murine Achilles te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The use of human recombinant hyaluronidase may therefore be particularly useful in the reactive or early disrepair phase, before irreparable structural damage has occurred. Fortunately, previous experimental studies have shown that depletion of GAGs from tendon fascicles does not decrease tensile stiffness 40 147 151 152. We, therefore, speculate that this treatment, which has been used in different medical applications for over 60 years, could be safe for tendons as well 153–155…”
Section: Methodological Considerationsmentioning
confidence: 86%
See 1 more Smart Citation
“…The use of human recombinant hyaluronidase may therefore be particularly useful in the reactive or early disrepair phase, before irreparable structural damage has occurred. Fortunately, previous experimental studies have shown that depletion of GAGs from tendon fascicles does not decrease tensile stiffness 40 147 151 152. We, therefore, speculate that this treatment, which has been used in different medical applications for over 60 years, could be safe for tendons as well 153–155…”
Section: Methodological Considerationsmentioning
confidence: 86%
“…On the other hand, drug treatment that directly targets the elevated GAG content might also be a very powerful tool. A potential treatment that has been mentioned recently for tendinopathies is human recombinant hyaluronidase, as it degrades HA, CS and DS from the ECM to preinjury levels 147 148. The removal of these excess GAGs can liberate the bound fluid and significantly reduce the fluid content, resulting in a lower IRP, thus enabling vascular re-expansion 101 140 149.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The TGF-β1 injection model was established by injecting 100 ​ng of TGF-β1 into the mice Achilles tendon on days 0 and 2 [ 60 , 61 ]. Rezvani et al.…”
Section: Animal Models Corresponding To Extracellular Matrix Synthesi...mentioning
confidence: 99%
“…Rezvani et al. showed that increased cellularity and rounded nucleus on day 6 [ 60 ]. Then, cartilage metaplasia and hyaluronan accumulation occurred in the tendon tissue on days 9 and 25.…”
Section: Animal Models Corresponding To Extracellular Matrix Synthesi...mentioning
confidence: 99%
“…Reviews cover the state of our understanding of normal and diabetic tendon healing and the role of the extracellular matrix in tendon development and homeostatis . A series of original research papers delves into tendon pathogenesis and healing, focusing on a broad range of topics: the effect of age and fatigue on tendon biomechanics, transcriptomics analysis of tendon healing, and treatment strategies that include hyaluronidase, pulsed electromagnetic fields, and parathyroid hormone . A collection of stem cell papers describes methods to generate and optimize stem cells and uses them to enhance tendon healing .…”
mentioning
confidence: 99%